Peran Kelompok Nelayan dalam Membangun Perilaku Adaptif dan Produktif pada Usaha Perikanan Masyarakat Pesisir di Nongsa Batam - Muthi Rizky Annisa; Kania Natasya Ayu Afriadi; Yusuf Roni; Yusuf Zainur Rahman; Ade Sarmini (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Fishermen groups play a strategic role in strengthening the adaptive capacity and productivity of coastal communities facing environmental and socioeconomic changes. This study examines the contribution of fishermen groups to fostering adaptive and productive behaviors among coastal fishing enterprises in Nongsa District, Batam City. A qualitative descriptive case study was conducted using field observations, documentation, and in-depth interviews with fishermen group administrators, traditional fishermen, and fisheries extension officers. The findings indicate that fishermen groups function as key community institutions by strengthening social cohesion, disseminating maritime weather forecasts and market information, facilitating access to government assistance and modern fishing equipment, providing training on navigation technology and business management, mediating fishing zone conflicts, and improving marine catch productivity. These institutional functions have enhanced fishermen’s capacity to respond to ecological uncertainty, optimize fishing activities, and diversify livelihood management. The study demonstrates that community-based organizations are essential in building resilience within coastal fisheries by integrating social support, technological innovation, and institutional collaboration. Strengthening fishermen groups through sustained policy support and capacity development is therefore critical to promoting sustainable coastal livelihoods amid increasing environmental and economic pressures.